2021
DOI: 10.3390/cells10082026
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Control of Liver Development

Abstract: During liver organogenesis, cellular transcriptional profiles are constantly reshaped by the action of hepatic transcriptional regulators, including FoxA1-3, GATA4/6, HNF1α/β, HNF4α, HNF6, OC-2, C/EBPα/β, Hex, and Prox1. These factors are crucial for the activation of hepatic genes that, in the context of compact chromatin, cannot access their targets. The initial opening of highly condensed chromatin is executed by a special class of transcription factors known as pioneer factors. They bind and destabilize hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 186 publications
(250 reference statements)
0
29
0
Order By: Relevance
“…Their progressive involvement culminates at the post-natal level with the establishment of the characteristic transcriptome of the adult hepatocyte. The FOXA family of proteins, composed by three members FOXA1, FOXA2 and FOXA3 (also known as HNF3, HNF3 and HNF3, respectively), is expressed early during endoderm patterning and is essential for liver development [6,8]. Another set of regulatory proteins almost concomitantly involved in hepatoblast specification is the GATA family of TFs, particularly GATA4 and GATA6.…”
Section: Cellular Signals and Pioneer And Non-pioneer Transcription F...mentioning
confidence: 99%
See 2 more Smart Citations
“…Their progressive involvement culminates at the post-natal level with the establishment of the characteristic transcriptome of the adult hepatocyte. The FOXA family of proteins, composed by three members FOXA1, FOXA2 and FOXA3 (also known as HNF3, HNF3 and HNF3, respectively), is expressed early during endoderm patterning and is essential for liver development [6,8]. Another set of regulatory proteins almost concomitantly involved in hepatoblast specification is the GATA family of TFs, particularly GATA4 and GATA6.…”
Section: Cellular Signals and Pioneer And Non-pioneer Transcription F...mentioning
confidence: 99%
“…To perform these complex and spatially coordinated functions hepatocytes must express a large complement of enabling genes. This gene expression signature is progressively established from early hepatic development through cell-to-cell signalling and a network of key transcription factors (TFs) and their activation or repression complexes, that shape up liver-specific gene expression [6]. After birth, an increasingly complex set of cross-regulated TFs, plus signalling systems such as WNT and Notch, and splicing regulators (SR), define the liver zonal architecture and consolidate mature hepatocellular function [2,[6][7][8]].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These domains provide the involvement of TRIM proteins transcriptional regulation, cytoskeletal organization, epithelial development, cell adhesion, and immune response [ 22 ]. Another retrieved transcription factor, HHEX, is involved in cell growth and differentiation, hepatic and pancreatic development, and anterior–posterior pattern specification via the Wnt signaling pathway [ 23 ]. Additionally, HHEX has been associated with type 2 diabetes, whereas zinc finger proteins are linked to the progression of various cancers [ 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide characterization of ESC-derived hepatocyte-like cells indicated that some genes are associated with metabolic processes such as small molecule metabolic processes or secondary metabolic processes [ 64 ]. Some transcription factors, such as FOXA1/2/3, HNF4α, and CEBPA can maintain hepatocyte maturation through a combined action [ 65 ]. In this study, we found that, in addition to signaling pathways for cell proliferation and DNA replication, newly enriched signaling pathways in hepatocytes between 72 to 96 hpf include metabolisms of pyrimidine, purine, nicotinate and nicotinamide, caffeine, glycine, serine and threonine, ABC transporters, and p53 signaling, which are known to function in metabolisms of lipid, protein and energy, cellular secretion, and detoxification.…”
Section: Discussionmentioning
confidence: 99%